Mechanical and Tribological Study on Aluminum Coatings with High-Pressure and Low-Pressure Cold-Spray Processes - Manap A.; Afandi N.F.; Mahalingam S.; Yusof S.N.A.; Mohd. Rosli Z. (MDPI, 2023)
Cold spray is a promising approach to repair all damages and defects in aluminum (Al) constituent elements. The study aims to investigate the mechanical and tribological properties of Al coatings deposited using high-pressure cold-spray (HPCS) and low-pressure cold-spray (LPCS) techniques. Al powder was sprayed on a cold-rolled plate of aluminum 1100, which was used as the substrate. The results showed that the micro-hardness of the LPCS Al coating reached up to 196.6 HV before the wear test compared to that of HPCS (174.3 HV). Moreover, more low friction coefficients obtained by LPCS (0.798) than HPCS (0.807) indicated good tribological properties with a high amount of oxide composition. Meanwhile, the wear studies reveal that the specific wear rate of the Al coating of LPCS (0.008) was lower than the HPCS (0.009) as the load increased from 3 N to 5 N, thus providing excellent wear resistance. Therefore, the results exhibited greater mechanical and tribological characteristics for Al coatings produced by the LPCS process than by the HPCS process. 2022 by the authors.